Sequence stratigraphic analysis of the late Permian Changhsingian platform marginal reef, Western Hubei, South China - Beichen Chen; Feng Wu; Xinong Xie; Ya Gao; Wang Xiao; Zhiyi Tang (Frontiers in Marine Science, 2024)
This study presents a comprehensive analysis of the late Permian platform marginal reefs in the Sichuan Basin, focusing on reefal lithofacies and sequence stratigraphic patterns. Field outcrop observations and rock sample analyses from the Jiantianba reef were conducted to establish an evolution model of sponge reef development and spatial distribution. Four stages of marginal carbonate platform were documented: open platform, gently sloping reef, steeply sloping reef, and reef bank system. Distinct lithofacies were identified in these stages, reflecting different depositional environments and growth rates. The gently sloping reef was composed of filled skeleton framestone, filled skeleton bafflestone, and micrite organism limestone, indicating limited reef-building capacity. In contrast, the lithofacies of steeply sloping reefs were composed of open skeleton framestone, open skeleton bafflestone, binding skeleton bafflestone, and benthic organism bindstone, indicating stronger reef-building ability. Based on depositional features and carbon isotopic trends, the reef strata were divided into two sequences. Sequence 1 corresponds to the formation of unit 1, and sequence 2 can be further divided into units 2 and 3. In unit 1, reefs developed in a relatively deeper-water setting. It was characterized by rich micrite limestone, forming a gentle margin. Unit 2 witnessed reef development in shallower waters. Early marine cementation and microbial clots were prevalent, contributing to form a steep margin. In the early stage of unit 3, reefs primarily developed in a tidal-controlled environment. Subsequently, reef strata experienced a transition to a wave-influenced environment, leading to the formation of a reef bank system. In general, sequence 1 mainly formed in a heterozoan-dominated factory, and reefs contributed to a relatively gently sloping platform margin. In contrast, sequence 2 formed in a photozoan-dominated factory, and reefs contributed to a relatively steeply sloping platform margin.